The genus Haplodrassus Chamberlin, 1922 in the Mediterranean and the Maghreb in particular (Araneae: Gnaphosidae) - Bosmans, Robert; Kherbouche-Abrous, Ourida; Benhalima, Souâd; Hervé, Christophe (Zootaxa, 2018)
The Haplodrassus species of the the Maghreb are revised. Six new species are described: H. dentifer Bosmans & Abrous, sp. n. (♂♀, Algeria, Morocco, Tunisia, Spain), H. longivulva Bosmans & Hervé, sp. n. (♂♀, Algeria, Morocco), H. lyndae Abrous & Bosmans, sp. n. (♂♀, Algeria, Morocco, Spain), H. ovatus Bosmans & Hervé, sp. n. (Tunisia, Algeria), H. securifer Bosmans & Abrous, sp. n. (♂♀, Algeria, Morocco, Tunisia, Portugal, Spain, France, Italy, Belgium) and H. triangularis Bosmans, sp. n. (♂♀, Morocco, Tunisia). The following new synonyms are proposed. Drassus corticalis Lucas, 1846, syn. n. and Drassus similis C.L. Koch, 1866, syn. n. were found to be junior synonyms of Drassus rufipes Lucas, 1846. Drassus parvulus L. Koch 1882, Drassodes acrotirius Roewer, 1928, Drassodes seditiosus Caporiacco, 1928, Drassodes parvicorpus Roewer, 1951 and Haplodrassus maroccanus Denis, 1956 are junior synonyms of Drassus omissus O.P.-Cambridge, 1872 syn. n. and this species is transferred to Haplodrassus comb. n. (taken out of the synonymy with H. morosus (O.P.-Cambridge, 1872, contra Levy, 2004). Drassodes nigroscriptus deminutus Simon, 1909 and Drassodes nigroscriptus Simon, 1909 are synonyms and the species is transferred to Haplodrassus comb. n. Haplodrassus isaevi Ponomarev & Tsvetkov, 2006 is a junior synonym of Haplodrassus orientalis (L. Koch), 1866 syn. n. comb. n. H. macellinus hebes (O.P.- Cambridge, 1874) is a synonym of Haplodrassus macellinus (Thorell, 1871) syn. n. Haplodrassus vignai Di Franco, 1996 is a synonym of H. macellinus (Thorell, 1871) (taken out of the synonymy of H. invalidus O.P.-Cambridge, 1872, contra Levy, 2004). H. gridellii Caporiacco, 1949 is taken out of the synonymy with H. pugnans (Simon, 1880) and synonymized with H. rufipes (Lucas, 1846) syn. n. (contra Levy, 2004). The following new combinations are proposed. Drassodes rhodanicus Simon, 1914 = Haplodrassus rhodanicus (Simon, 1914), comb. n. Drassus crassipes Lucas, 1846 = Haplodrassus crassipes (Lucas, 1846) comb. n. The following new status is proposed: Haplodrassus typhon (Simon, 1878) is removed from the synonymy of H. macellinus Thorel, 1871, is declared a valid species, a female lectotype is designated and the unknown male is described. Drassodes severus L. Koch, 1839 and Drassodes spinicrus Caporiacco, 1928 are declared nomina dubia. The female of H. rhodanicus is described for the first time, and the male illustrated for the first time. All Haplodrassus species occurring in the Maghreb are redescribed as well as Haplodrassus macellinus (Thorell, 1871), only occurring in S.W. Europe and deleted from the North African list. New distribution data and photos of other European Haplodrassus species are presented.